STUDI TENTANG PERKEMBANGAN DAN MAKNA MOTIF SONGKET BATU BARA DI SUMATERA UTARA - ANINDYA PRASTIWI, Dra. Zubaidah, M. Pd, Drs. Erwin, M.Sn (Serupa The Journal of Art Education, 2014)
This study is aimed to provide an overview on the development of visual and written of songket Batubara motifs and the philosophical meanings of each motif. This research is a descriptive qualitative research. From the research, it can be concluded that the development or change of songket Batubara motifs began around 1970. Old motifs are pucuk rebung, pucuk betikam, tolop berantai, pucuk kol, pucuk pandan and pucuk perak. New motifs are nasi bertabur, bunga tunggal and bunga mawar. Motifs that changed are pucuk rebung, pucuk betikam and tolop berantai. Pucuk Rebung, Tolop Berantai and Pucuk Betikam have the same meaning that illustrates how to behave in the community and how to be a good and wise leader. While Pucuk Kol, Pucuk Pandan dan Bunga Cempaka are an overview of natural resources and as symbolic of this nature. Gigi hiu (Shark teeth) motif is a symbol of the source of income of Batubara society.Keywords: meaning of songket motifs, songket batubara, development of songket motifs